Enhanced mobility and environmental stability in all organic field‐effect transistors: The role of high dipole moment solvent. Issue 21 (23rd August 2013) - Ukah, Ndubuisi B.; Senanayak, Satyaprasad P.; Adil, Danish; Knotts, Grant; Granstrom, Jimmy; Narayan, K. S.; Guha, Suchi
ABSTRACT Low‐operating voltage, high mobility, and stable organic field‐effect transistors (OFETs) using polymeric dielectrics such as pristine poly(4‐vinyl phenol) (PVP) and poly(methyl methacrylate) (PMMA), dissolved in solvents of high dipole moment, have been achieved. High dipole moment solvents such as propylene carbonate and dimethyl sulfoxide used for dissolving the polymer dielectric enhance the charge carrier mobilities by three orders of magnitude in pentacene OFETs compared with low dipole moment solvents. Fast switching circuits with patterned gate PVP‐based pentacene OFETs demonstrated a switching frequency of 75 kHz at input voltages of |5 V|. The frequency response of the OFETs is attributed to a high degree of dipolar‐order in dielectric films obtained from high‐polarity solvents and the resulting energetically ordered landscape for transport. Remarkably, these pentacene‐based OFETs exhibited high stability under bias stress and in air with negligible shifts in the threshold voltage. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2013, 51, 1533–1542